Antibacterial Activity of Secondary Metabolits Isolated from Mangrove Leaves Sonneratia alba - Verly Dotulong; Lena Jeane Damongilala; Djuhria Wonggo; Lita A.D.Y. Montolalu (Jurnal Ilmiah Sains, 2022)
Mangroves Sonneratia alb is a plants that grows in tidal areas with considerable environmental pressure. This condition causes the plant to synthesize secondary metabolites that have certain bioactivity to protect it self from destruction. The purpose of this study was to isolate antibacterial secondary metabolites from the mangrove leaves of  S.alba. The method applied was to isolate secondary metabolites from the ethyl setate fraction using column chromatography and identified the results of isolation with thin layer chromatography until a pure isolate was obtained. Pure isolates were characterized in structure using HNMR, IR and LC-MS spectroscopy. The resulting isolate in the form of methanol-soluble oil had the molecular formula C24H38O4 with the name Di(2-ethylhexyl)phthalate. The antibacterial activity of this compound was the same as the antibacterial activity of amoxicillin as a positive control, namely the diameter of the inhibition zone was 7 mm at a sample concentration of 0,21%.Aktivitas Antibakteri Metabolit Sekunder yang Diisolasi dari Daun Mangrove Sonneratia albaABSTRAKMangrove termasuk Sonneratia alba adalah tumbuhan yang tumbuh pada daerah pasang surut dengan tekanan lingkungan yang cukup besar, keadaan ini menyebabkan tumbuhan mangrove menyintesis metabolit sekunder yang mempunyai bioaktivitas tertentu untuk melindungi diri dari perusakan. Tujuan dari penelitian ini adalah mengisolasi metabolit sekunder antibakteri  dari daun mangrove  S.alba.. Metode yang digunakan adalah mengisolasi metabolit sekunder pada fraksi etil asetat menggunakan kromatografi kolom dan identifikasi hasil isolasi dengan kromatografi lapis tipis hingga didapatkan isolat murni. Isolat murni dikarakterisasi strukturnya menggunakan spektroskopi HNMR, IR dan LC-MS. Isolat yang dihasilkan berupa minyak yang larut dalam metanol mempunyai rumus molekul C24H38O4 dengan nama Di(2-etilhexil)fthalat. Aktivitas antibakteri dari senyawa ini  sama dengan aktivitas antibakteri amoxicilin sebagai kontrol positif yaitu diameter zona hambat sebesar 7 mm pada konsentrasi sampel 0,21%.Kata kunci: Aktivitas antibakteri; metabolit sekunder; Sonneratia alba